2021
DOI: 10.6007/ijarbss/v11-i5/9863
|View full text |Cite
|
Sign up to set email alerts
|

The Nexus between Financial Development and Economic Growth in China

Abstract: The relationship between financial development and economic growth has been subject to the considerable debate in the literature of development and growth. Hence, this study aims to investigate the long-run relationship between financial development and economic growth of China over the period 1988 to 2018. This study employed Johansen's Cointegration and Granger Causality analysis to achieve the objectives of the study. The findings of this study indicate there is a long-run relationship between financial dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
0
0
Order By: Relevance
“…It has been empirically found that financial development and trade openness foster economic growth in the three selected Northeast Asian countries, and this implies the importance of financial development and trade openness to the economy of these countries. Our findings are consistent with the conclusions of Vo et al (2020) and Cheng-Sze et al (2021) who argued that economic growth in China is facilitated by financial development. However, our results are contrary to Liu & Hsu (2006), who concluded that financial development has a negative impact on economic growth in Japan and the Republic of Korea, while Hwang (2020) claimed that the effect of financial development on the economic growth of the Republic of Korea may be either positive or negative depending on the rate of private credit.…”
Section: Discusionsupporting
confidence: 93%
See 2 more Smart Citations
“…It has been empirically found that financial development and trade openness foster economic growth in the three selected Northeast Asian countries, and this implies the importance of financial development and trade openness to the economy of these countries. Our findings are consistent with the conclusions of Vo et al (2020) and Cheng-Sze et al (2021) who argued that economic growth in China is facilitated by financial development. However, our results are contrary to Liu & Hsu (2006), who concluded that financial development has a negative impact on economic growth in Japan and the Republic of Korea, while Hwang (2020) claimed that the effect of financial development on the economic growth of the Republic of Korea may be either positive or negative depending on the rate of private credit.…”
Section: Discusionsupporting
confidence: 93%
“…China, which is known as one of the world's largest economies, has implemented economic reforms since 1978. China's financial system is highly regulated by the government (Cheng-Sze et al, 2021). The growth rate of the Chinese economy has slowed down visibly since the global financial crisis of 2008-2009(Murach et al, 2022.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation